Meta-Motivation and its Relation to Emotional Labour and Mental Fatigue among Pre-service Practitioners at Yarmouk University - Al Rababah, Hamzeh; Al-Momani, Abeer (Dirasat: Educational Sciences, 2022)
This study aims at investigating meta-motivation and its relation to emotional labour and mental fatigue among a sample of (391) students randomly selected from Yarmouk university during the first semester of the academic year 2019/2020. To achieve the aims of the study, Chen's (1995) meta- motivation scale, Johansson and Runback's (2014) mental fatigue scale, and emotional labour scale were used in the study. The results of the study revealed high meta-motivation level, high deep emotional labour level, moderate surface emotional labour level, and low mental fatigue level. The results also revealed that there were no statistically significant differences in meta-motivation level, surface and deep emotional labour and mental fatigue due to gender. There were no statistically significant differences in meta-motivation level and deep emotional labour due to the specialization. Finally, the results revealed a positive correlation between meta-motivation and surface and deep emotional labour, and a negative correlation between meta-motivation and mental fatigue.